1979
DOI: 10.1007/bf00280586
|View full text |Cite
|
Sign up to set email alerts
|

Stability regions in predator-prey systems with constant-rate prey harvesting

Abstract: We analyze the global behavior of a predator-prey system , modelled by a pair of nonlinear ordinary differential equations, under constant-rate prey harvesting . By methods an alogous to those used to study predator harvesting, we characterize the theoretically possible structures and transitions. With the aid of a computer simulation we construct examples to show which of the se transitions can be realized in a biologically plausible model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 2 publications
0
75
0
1
Order By: Relevance
“…There is a positive equilibrium (x * , y * ) = (20,15). By Corollary 33, there is a critical value τ 0 = 0.8256, the equilibrium (x * , y * ) is stable when τ < 0.8256.…”
Section: Gause Models With Prey Harvesting and Delayed Prey Specific mentioning
confidence: 90%
See 3 more Smart Citations
“…There is a positive equilibrium (x * , y * ) = (20,15). By Corollary 33, there is a critical value τ 0 = 0.8256, the equilibrium (x * , y * ) is stable when τ < 0.8256.…”
Section: Gause Models With Prey Harvesting and Delayed Prey Specific mentioning
confidence: 90%
“…As Nakaoka et al [69] showed that a LotkaVolterra predator-prey model with delays in the specific growth terms for both species can exhibit chaotic behavior, I expect that other predator-prey models with multiple delays could have similar complex dynamics. (ii) Delayed predator-prey models with both predator and prey harvesting (see Brauer and Soudack [14,15], Myerscough et al [68], and Hogarth et al [53] for some ODE models). I suspect that more degenerate bifurcations, such as fold-Hopf, Hopf-Hopf, and degenerate Bogdanov-Takens bifurcations (Kuznetsov [57]), may occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several papers that deal with predator-prey system subject to a harvest (Brauer & Soudack 1978, 1979a, 1979b, 1981, 1982.…”
Section: Introductionmentioning
confidence: 99%